PELAKSANAAN PERJANJIAN PEMBIAYAAN MULTIGUNA PADA PT. MITRA PINASTHIKA MUSTIKA FINANCE (MPM) PEKANBARU - Wan Rahmatullah Ramadhan; Firdaus Firdaus; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The high public need for consumptive goods and the need for funds(multipurpose) is characterized by limited ability or purchasing power incash/cash, making consumer finance institutions the preferred choice of thecommunity, thus making consumer finance institutions (consumer finance) haveshown an active role in supporting the economy and business in Indonesia. PT.Mitra Pinastika Musthika Finance Pekanbaru Branch, is a finance company thatcarries out its business activities in the field of consumer finance, which focuses onfinancing new motorcycles and used motorcycles, also provides loan funds withmotorcycle guarantees from debtors known as multipurpose financing, thepayment of which is done in installments or periodically by consumers.The purpose of this study was to determine and understand theimplementation of consumer financing agreements at PT. Mitra PinastikaMusthika Finance Pekanbaru Branch, as well as solving problems that arise ifthere is a default by the debtor in the implementation of the consumer financingagreement.In this study, empirical/sociological juridical methods were used. surveybecause the author went directly to the research location to get primary data,which was then analyzed descriptively, which prioritizes observations(observations) on the actual symptoms of events.The results of the study provide an overview of the consumer financingagreement, especially multipurpose, which is a debt agreement between PT. MitraPinastika Musthika Finance Pekanbaru Branch, and the consumer, the delivery oftheir belongings in this case the motorcycle BPKB and other documents ascollateral, the delivery of collateral is carried out based on trust. Consumerfinancing agreements are made in written form using standard agreements.Delayed installment payments are the debtor's obligation not because of thedebtor's intention to delay installment payments, but the debtor dies during thecontract period, leaving 3 (three) installment obligations. To terminate aproblematic contract is taken by way of deliberation to reach consensus.It can be concluded that consumer finance institutions are an alternative toobtain loan funds and other necessities, with the death of the debtor during thecontract period is categorized as an act of default.Keywords: Multipurpose Consumer Financing, Default